Crystallization and preliminary crystallographic analysis of the ADP-ribosyltransferase HopU1. Corrigendum - Lin, Yan (International Union of Crystallography, 2010)
A correction is made to the article by Lin et al. [(2010). Acta Cryst. F66, 932–934].